EFEK REGENERASI LARUTAN NaOH PADA DEASETILASI KITIN TERHADAP DERAJAT DEASETILASI KITOSAN - Ahmad Budi Junaidi; Arini Rahmadani (Jurnal Sains dan Terapan Kimia, 2008)
The effect of regenerating NaOH solution in multistage deacetylation of chitin has been done. The process of deacetylation was carried out in multistages process, one of the chitin was on in 110 0C for 1x3 hours (chitosan I), 2x1.5 hours ( chitosan II) and 3x1 hours (chitosan III). The deacetylation degree of chitosan was determined by FTIR method, The results showed that chitosan prepared by regeration of NaOH solution causes an increase deacetylation degree of chitosan, deacetylation degree of chitosan I, II and III are 68.05%, 84.23% and 90.32% respectively.  Keywords: chitin, chitosan, regeration of NaOH solution, multistage deacetylation, deacetylation degree.